2009
DOI: 10.1002/jrs.2406
|View full text |Cite
|
Sign up to set email alerts
|

Vibrational spectroscopic studies and ab initio calculations of phenyl phosphate disodium salt

Abstract: The Fourier-transform infrared and Fourier-tranform Raman spectra of phenyl phosphate disodium salt were recorded and analyzed. The surface-enhanced Raman scattering (SERS) spectrum was recorded in a silver colloid. The vibrational wavenumbers of the compound were computed using the Hartree-Fock/6-31G * basis and compared with the experimental values. The molecule is adsorbed on the silver surface with the benzene ring in a tilted orientation. The presence of the phenyl ring and the phosphate group vibrations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 65 publications
(67 reference statements)
1
11
0
Order By: Relevance
“…The calculated mean first hyperpolarizability (b o ) of the compounds DCBN and m-BBN are 5.22178 Â 10 À30 e.s.u and 1.85669 Â 10 À30 e.s.u, respectively, which is comparable with the reported values of similar derivatives [38,39]. The components of first hyperpolarizability for DCBN and m-BBN are listed in Table 11.…”
Section: Prediction Of First Hyperpolarizability (B O )supporting
confidence: 59%
“…The calculated mean first hyperpolarizability (b o ) of the compounds DCBN and m-BBN are 5.22178 Â 10 À30 e.s.u and 1.85669 Â 10 À30 e.s.u, respectively, which is comparable with the reported values of similar derivatives [38,39]. The components of first hyperpolarizability for DCBN and m-BBN are listed in Table 11.…”
Section: Prediction Of First Hyperpolarizability (B O )supporting
confidence: 59%
“…[239] Anto and coworkers measured and analyzed the FT-IR and FT-Raman spectra of phenylphosphate disodium salt, and they also measured the SERS spectrum as a silver colloid. [240] They found that the presence of the phenyl ring and the phosphate group vibrations in the SERS spectrum contains information regarding the interactions between the phenyl and phosphate groups on the silver surface. Ayyappan et al obtained the FT-IR and FT-Raman spectra of 3,5-dichlorophenylboronic acid in the solid phase.…”
Section: Methods Of Data Analysismentioning
confidence: 99%
“…Ando, Matazo and Santos carried out a systematic Raman experimental and theoretical spectroscopic study of the interaction between N , N ‐dimethylaniline (DMA) and sulfur dioxide (SO 2 ), where the formation of a deep red oil by the reaction of SO 2 with DMA is an evidence of the charge transfer nature of the DMA–SO 2 interaction . Anto and coworkers measured and analyzed the FT‐IR and FT‐Raman spectra of phenylphosphate disodium salt, and they also measured the SERS spectrum as a silver colloid . They found that the presence of the phenyl ring and the phosphate group vibrations in the SERS spectrum contains information regarding the interactions between the phenyl and phosphate groups on the silver surface.…”
Section: Vibrational Studies In Chemistrymentioning
confidence: 99%
“…Many organic molecules containing conjugated π electrons and characterized by large values of molecular first hyperpolarizabilities have been analyzed by means of vibrational spectroscopy. [21] Nonlinear optics deals with the interaction of applied electromagnetic fields in various materials to generate new electromagnetic fields, altered in frequency, phase or other physical properties. [22] Organic molecules able to manipulate photonic signals efficiently are of importance in technologies such as optical communication, optical computing and dynamic image processing.…”
Section: Introductionmentioning
confidence: 99%